The creative city does not exist - Marianna D'Ovidio (Ledizioni, 2016)
Every city wants to become creative, perhaps even the most creative ever. But what does it mean to be a creative city? What images take shape as a consequence? What sort of city do we envisage? Which one are we actually building? In a journey that starts with Blade Runner and passes through English punk, Milanese creative workers and Star Wars, the book explores the features and outcomes of the creative city, penetrating its dark side but also identifying its assets. In the future, cities must be guided by a vision of a creative city able to be inclusive yet competitive, to open new public spaces and to be socially innovative. This book presents some of the tools that allow us to look at the city as a place whose air makes people free.